2020
DOI: 10.1093/ecco-jcc/jjaa171
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Translational Gastrointestinal Research in the Era of COVID-19

Abstract: Spread of the novel coronavirus SARS-CoV-2 has resulted in a global pandemic that is affecting the health and economy of all WHO regions. Clinical and translational research activities have been impacted drastically by this global catastrophe. In this document we provide a suggested roadmap for resuming gastrointestinal translational research activities, emphasizing physical distancing and use of personal protective equipment. We discuss modes of virus transmission in enclosed environments (including clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The history of the 1918 flu pandemic taught valuable lessons about an ordered approach (6). Clear communication and transparency supports compliance with pandemic policies, perseverance with risk-mitigation steps avoids the consequences of a premature cessation of restrictions, and a phased re-opening is recommended (Figure 4) (14). Despite a lack of a coordinated national response, academic medical centers adopted similar approaches to managing research programs with a goal of keeping our workforce and research participants safe by reducing the spread of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The history of the 1918 flu pandemic taught valuable lessons about an ordered approach (6). Clear communication and transparency supports compliance with pandemic policies, perseverance with risk-mitigation steps avoids the consequences of a premature cessation of restrictions, and a phased re-opening is recommended (Figure 4) (14). Despite a lack of a coordinated national response, academic medical centers adopted similar approaches to managing research programs with a goal of keeping our workforce and research participants safe by reducing the spread of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Phase 4 enables all CTR activities to resume. Figure modified from version in Nayeri et al [14]. 6 Flume et al…”
Section: Discussionmentioning
confidence: 99%
“…Research during the COVID-19 pandemic employs more online survey research and also systematic literature review methods, both of which do not require face-to-face contact with informants and respondents or work in laboratories so that research with this method is widely found and is an adaptation strategy for researchers at universities in dealing with the COVID-19 pandemic [42], [43]. Moreover, research that employs secondary data with both qualitative and quantitative analysis is also the choice of researchers.…”
Section: Discussionmentioning
confidence: 99%